2002
DOI: 10.1073/pnas.222433299
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic effects of thioflavin S-positive amyloid deposits in transgenic mice and Alzheimer's disease

Abstract: Despite extensive deposition of putatively neurotoxic amyloid-␤ (A␤) protein in the brain, it has not been possible to demonstrate an association of A␤ deposits with neuronal loss in Alzheimer's disease (AD), and neuronal loss is minimal in transgenic mouse models of AD. Using triple immunostaining confocal microscopy and analyzing the images with the cross-correlation density map method from statistical physics, we directly compared A␤ deposition, A␤ morphology, and neuronal architecture. We found dramatic, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
146
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(156 citation statements)
references
References 40 publications
7
146
0
1
Order By: Relevance
“…Other methods that look at positional organization of neurons related to pathological conditions include early work by Benes and Bird (24), in which they applied computerassisted stereomorphometric analyses to neuron (x,y) locations and found that the anterior cingulate cortex of schizophrenic patients may contain aggregates of neurons, particularly in layer II. Also, Urbanc et al (25) used a crosscorrelation density-map method to study spatial relationships between the position and morphology of plaques with changes in neuronal architecture and revealed a focal neuronal toxicity associated with thioflavin S-positive plaque deposits in both AD and transgenic mice. Others, such as Casanova and Buxhoeveden, developed a method to quantify individually identified microcolumns, applying it to different human brain disorders (e.g., autism) (9)(10)(11)27), ʈ and to identify microcolumnar organization across species (28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Other methods that look at positional organization of neurons related to pathological conditions include early work by Benes and Bird (24), in which they applied computerassisted stereomorphometric analyses to neuron (x,y) locations and found that the anterior cingulate cortex of schizophrenic patients may contain aggregates of neurons, particularly in layer II. Also, Urbanc et al (25) used a crosscorrelation density-map method to study spatial relationships between the position and morphology of plaques with changes in neuronal architecture and revealed a focal neuronal toxicity associated with thioflavin S-positive plaque deposits in both AD and transgenic mice. Others, such as Casanova and Buxhoeveden, developed a method to quantify individually identified microcolumns, applying it to different human brain disorders (e.g., autism) (9)(10)(11)27), ʈ and to identify microcolumnar organization across species (28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated whether the small repulsive force detected between astrocytes and plaques, strong enough to cause the nearest astrocytes to move a few microns, would disturb g(r) at heavier plaque loads. Whereas in APP/PS1 mice the percentage of brain covered by thioflavin or methoxy-labeled plaques can reach 1%, in humans it ranges between 0.8-6.0%, with an average of around 3% (11,12).…”
Section: Tiered Analysis Of Astrocyte Domain-volume Distribution Aroundmentioning
confidence: 99%
“…Fibrillar amyloid (A␤) deposition, one of the hallmarks of AD, is commonly associated with dystrophic neurites [41][42][43] and aberrant sprouting, [44][45][46][47] as well as increased curvature of dendritic processes. [48][49][50] However, only A␤ deposition in certain areas but not others correlates well with the degree of cognitive dysfunction. 46,[51][52][53][54][55] Furthermore, in transgenic mouse models of AD it has been shown that cognitive dysfunction may occur even before plaque deposition.…”
Section: Imaging Structural Plasticity Of Synapses In Mouse Models Ofmentioning
confidence: 99%